Knowing the rules can effectively enhance plastic waste separation on campus - Uehara, Takuro; Asari, Misuzu; Sakurai, Ryo (Frontiers in Sustainability, 2022)
Although proper plastic waste separation is critical to efficient disposal, people do not always comply with designated rules, possibly resulting from a lack or misunderstanding of the correct rules related to local variability. Accordingly, this study aimed to understand how learning the plastic waste separation rules changed college students' behavior on campus, besides how said knowledge spreads across campuses. To evaluate the impact, quasi-experiments were conducted from May to July 2022, including a hybrid of before–after and treatment–control designs. The treatment group included college students at a university in Japan (N = 295 and 188 for the first and second surveys, respectively); the control group also included college students in the same region (N = 395 and 219 for the first and second surveys, respectively). Before learning the rules, 12.8% of the treatment group followed the correct rules. After acquiring the rules, this number increased to 38.3%. The difference-in-differences analysis verified its statistically significant improvement over the control group. Structural equation models based on the theory of planned behavior before and after learning the rules revealed that the intention–behavior gap was bridged by the learning, indicating limitations due to a lack of knowledge. The best–worst scaling showed that habits should be targeted to further improve separation behaviors; whereas an egocentric network analysis demonstrated that knowledge spread among peers, albeit to a limited extent. In summary, this study revealed that knowing designated rules is a simple but effective approach to enhancing plastic waste separation in a certain context.